Analisis Tata Kelola Layanan Indeks Kepuasan Masyarakat Menggunakan Kerangka Kerja Itil V4 Pada Dinas Penanaman Modal Dan Ptsp Kota Pangkalpinang - Zelika Apriliani; Tata Sutabri (STIE Amkop Makassar, 2023)
The community satisfaction index is the main focus in determining the success of an agency's service program. This research uses the ITIL v4 (Information Technology Infrastructure Library) framework to analyze the governance of community satisfaction index services in the one-stop capital investment and integrated services department in the city of Pangkalpinang. This research method uses a quantitative method with observation stages and questionnaires distributed to users, IT administrators and IT managers. The results of the service analysis in the form of measures of information technology governance can be used as policy formulation documents related to policies The ITIL v4 framework helps analyze the level and size of community satisfaction index service governance using the ITIL v4 framework so that it functions as an evaluation for service providers to continue to improve the quality of services at the Pangkalpinang City investment and PTSP services